การเชื่อมโยงเนื้อหา "นวนิยาย" ในสื่อสิ่งพิมพ์และในสื่อละครโทรทัศน์ - ปิยะพิมพ์ สมิตดิลก (จุฬาลงกรณ์มหาวิทยาลัย, 1998)
The objectives of this research were to study the form of intertextuality of novel between printed media and television soap opera and to study the factors related to this intertextuality between both media. The concept and theoretical framework of this research based on the Novel theory, Soap opera Production Theory, Genre Analysis such as Formula, Narration, Intertextuality and Convention/Invention Concept. This research included the study on documentary and video tapes of "Sai Sri Ploeng" and "Yam Mue Lom Phad Huan". The research found that the Novel and television Soap opera has the intertext between each other such as Conceptualization & Visualization, Narration, Character and Characterization and Format of Novel and Soap Operas. The form of intertextuality can be divided by 2 perspectives : Convention/Repetition and Invention/ Variation. Factors related to this intertext could be attributed to Nature of media, Stardom and Difference between Genres.